IMPROVING LEASE RELATIONS THROUGH FURTHER DEVELOPMENT OF DIGITAL INFRASTRUCTURE - Baxodirov Alisher Komilovich (Web of Journals Publishing, 2025)
This article analyzes the role of modern technologies in simplifying leasing processes, increasing transparency, and ensuring efficiency. It explores the possibilities of managing lease agreements based on digital platforms, blockchain, and smart contracts while also highlighting existing problems and providing practical recommendations for their solutions.
Keywords: Digital infrastructure, lease relations, digitalization, smart contracts, blockchain, transparency, innovative approach, legal aspects, economic efficiency, digital platforms.